Performance: Views of Interpersonal Communication and Compensation - Yogy Syaputra Jaya; Iceu Gustina; M. Junestrada Diem (Journal Of Economic Cluster, 2024)
The purpose of this study was to determine the effect of interpersonal communication and compensation on employee performance at the distributor unit adi blessing gunung megang muara enim. The population in this study was 35 employees and the sample used saturated sample technique, so the sample in this study was 35 employees at the distributor unit adi blessing gunung megang muara enim. The analysis technique used is multiple linear regression with hypothesis testing using the t test and F test. The results of this study indicate that: (1) There is an effect of Interpersonal Communication on Employee Performance. (2) There is an effect of Compensation on Employee Performance. (3) There is an effect of Interpersonal Communication and Compensation on Employee Performance. The conclusion shows that both partially and simultaneously Interpersonal Communication and Compensation affect Employee Performance.